Exploring the job demands and resources and work-related sense of coherence of preschool educators working with children in need of special support - Veronica Semelius Granevald; Monika Vinterek; Lotta Strömsten (Journal of Early Childhood Education Research)
Inclusion of children needing special support presents challenges for preschool educators. Understanding factors that enhance their well-being can improve their ability to meet all children’s needs. This cross-sectional study investigated 90 preschool educators perceived job demands and resources related to working with children in need of special support, and work-related sense of coherence (comprehensibility, manageability, meaningfulness). Analyses of group differences between preschool teachers and child carers revealed no significant differences in the experience of job demands and resources but preschool teachers reported a higher degree of meaningfulness at work compared to child carers. Correlation analyses showed that job resources were all intercorrelated and either inversely correlated or uncorrelated with job demands. Job demands were also inversely correlated to sense of coherence. Linear regression results indicated that a higher work-related sense of coherence and self-perceived control predicted lower self-perceived job demands, even after controlling for social support, growth/development, child group size and insufficient reflection time. This study underscores the need to integrate a sense of comprehensibility, manageability, and meaningfulness at work to improve well-being and to cope with the emotional, cognitive, and organisational demands of working with children needing special support.